Desempenho de cultivares de trigo duplo propósito sob doses de adubação nitrogenada e regimes de corte - Hastenpflug, Marcel (2009)
The use of coul season cereals with dual purpose is an excellent alternative for croplivestock integration system, usually used in small properties in South Brazil, as it enables the production of fodder plant associated with the production of grains. Although there are commercial wheat cultivars of dual purpose developed for Rio Grande do Sul State, it is necessary to evaluate them more appropriately considering the soil and climate conditions of Paraná State. The objective of this study was to evaluate the income of grains and their quality, as well as the forage production and chemical composition of dual purpose cultivars of wheat under different rates of nitrogen fertilization and management of system cuts. The experiment was carried out at the experimental area of the Federal Technological University of Paraná, Dois Vizinhos Campus, and the experimental design was a randomized blocks with sowings bands and three replicates. The studied factors were: four cultivars of dual purpose wheat (BRS Figueira, BRS Guatambu, BRS Tarumã, and BRS Umbu); increased rates of nitrogen fertilization (0, 45, 90, 135, and 180 kg ha-1) applied to the plots; management of cuts simulating grazing (without cut, with one cut, and two cuts) applied to sub-plots. The evaluated variables were: leaf blade proportion (LP) in the forage; forage production (FP); crude protein (CP), in vitro digestibility of organic matter (IVDOM), and total digestible nutrients (TDN) in the dry matter; spike weight (SW); number of spiklets per spike (NS); number of grains per spiklet (NG); grain yield and the hectoliter weight (HW). Data were submitted to analysis of variance, through F test, at a 5% probability error. The qualitative variables were compared by the Duncan test and the quantitative variables by regression analysis. The grain yield found for the cultivars and managements studies averaged 1.202,23 kg ha-1, with an average hectoliter weight of 74.3 kg hL-1. Rates of nitrogen fertilization did not influenced grain yield. The cultivars of half-delayed cycle (BRS Figueira and BRS Umbu) presented greater yield of grain (2.067,2 e 2.075,8 kg ha-1, respectively) than others; however, this income decreased severely as a function of the cuts. The nitrogen fertilization significantly influenced the FP and CP, which presented a linear growth as N fertilization rate increased. Cultivars of delayed-precocious cycle (BRS Guatambu and BRS Tarumã) presented lower total FP (1230,6 and 714 kg ha-1, respectively) than those of half-delayed cycle (BRS Figueira with 1.661,5 and BRS Umbu with 1.686,7 kg ha-1); however, they presented highest chemical quality, measured by CP and IVDOM. These results indicate that cultivars of delayedprecocious cycle are more adapted to the dual purpose management, because although they present lower total FP, their quality is higher. Moreover, they had shown a greater regrowth capacity after cuts, as they presented a lower decrease in grain yield.